2016
DOI: 10.21037/acs.2016.03.07
|View full text |Cite
|
Sign up to set email alerts
|

Uniportal thoracoscopic surgery: from medical thoracoscopy to non-intubated uniportal video-assisted major pulmonary resections

Abstract: The development of thoracoscopy has more than one hundred years of history since Jacobaeus described the first procedure in 1910. He used the thoracoscope to lyse adhesions in tuberculosis patients. This technique was adopted throughout Europe in the early decades of the 20 th century for minor and diagnostic procedures.It is only in the last two decades that interest in minimally invasive thoracic surgery was reintroduced by two key technological improvements: the development of better thoracoscopic cameras a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 52 publications
0
31
0
2
Order By: Relevance
“…First thoracoscopy was performed by Jacobaeus in 1910 [14]. VATS further developed with the availability of endoscopic linear mechanical staplers and thoracoscopic cameras from thoracoscopy [15]. Conventional VATS included 3-4 ports, and some studies have reported using a uniport approach during surgery [16].…”
Section: Discussionmentioning
confidence: 99%
“…First thoracoscopy was performed by Jacobaeus in 1910 [14]. VATS further developed with the availability of endoscopic linear mechanical staplers and thoracoscopic cameras from thoracoscopy [15]. Conventional VATS included 3-4 ports, and some studies have reported using a uniport approach during surgery [16].…”
Section: Discussionmentioning
confidence: 99%
“…S et al (48). Described and introduced by many authors over the last few years methodology of non-intubation single-port and conventional VATS, performed under potentiated local anesthesia of breathing lung has increased the possibilities for these methods to be applied to patients with contraindications for general anesthesia with one lung ventilation (6,8,13,17,(49)(50)(51)(52)(53)(54)(55)(56)(57)(58). All authors engaged with the topic claim, and we totally support them in our study, that there is no better way to deal with MPE than talc poudrage pleurodesis, performed together with a diagnostic assessment done by VATS methods (1, 2, 4, 6-11, 16-20, 29, 32, 37, 38, 43, 47, 50, 56, 59-62).…”
Section: Presentationmentioning
confidence: 99%
“…Huang et al haben in einem aktuellen Paper sehr ausführlich die verschiedenen Schritte der VATS-Manschettenresektionen beschrieben [30]. Ebenfalls 2013 beschrieben Gonzalez-Rivas et al die erste uniportale (single port) VATS-Lobektomie und zuletzt die "non-intubated-uniportal"-VATS-Resektion mit der gleichen Nahttechnik [12,31]. Vorteile der uniportalen VATS sind der…”
Section: Vats-manschettenresektion/single-port-vats/ Roboterchirurgieunclassified